Proceedings of the 15th International Joint Conference on Computer Vision, Imaging and Computer Graphics Theory and Application 2020
DOI: 10.5220/0008979800450052
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Semantic Perceptual Space of Synthetic Textures on an Ultrasonic based Haptic Tablet

Abstract: This paper aims to investigate the semantic perceptual space of synthetic tactile textures rendered via an ultrasonic based haptic tablet and the parameters influencing this space. Through a closed card sorting task, 30 participants had to explore 32 tactile-only textures and describe each texture using adjectives. A factorial analysis of mixed data was conducted. Results suggest a 2 dimensional space with tactile textures belonging to a continuum of rough to smooth adjectives. Influence of waveform and amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…Will the limited range of variable features on a haptic screen result in changes to the most salient perceptual axes? With this in mind, Dariosecq et al recently compared verbal descriptions of artificial textures to those used for real ones in earlier perceptual space studies [21]. Their artificial textures consisted of sinusoidal and square variations in friction on an ultrasonic friction modulation screen.…”
Section: Perceptual Dimensions Of Textures For Haptic Displaysmentioning
confidence: 99%
“…Will the limited range of variable features on a haptic screen result in changes to the most salient perceptual axes? With this in mind, Dariosecq et al recently compared verbal descriptions of artificial textures to those used for real ones in earlier perceptual space studies [21]. Their artificial textures consisted of sinusoidal and square variations in friction on an ultrasonic friction modulation screen.…”
Section: Perceptual Dimensions Of Textures For Haptic Displaysmentioning
confidence: 99%
“…Several studies revealed a two-dimensional space, one used superimposed dual-frequency vibrations on a handheld device [53], while another provided amplitudemodulated vibrotactile stimuli on a voice-coil actuator [54]. Others varied waveform, amplitude, and spatial period [34], [38], [55], or fundamental and overtone spatial frequencies and amplitudes [56] on friction-modulation displays.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Friesen et al, the lower frequency signals were identified as "bumpy" [36]. Dariosecq et al found that spatial period, which is related to frequency, acted as a modulator of different degrees of roughness [55]. A study conducted by Vardar et al showed that the perceived roughness of virtual textures generated via electrostatic forces follows an inverted U-shaped curve as a function of groove width at the macro-textural scale [38].…”
Section: Discussionmentioning
confidence: 99%
“…Kalantari et al [15] determined the size of the smallest perceived texture. Dariosecq et al [9] investigated the semantic perceptual space of tactile textures rendered and the parameters influencing this space. Researchers have also proposed different applications to strengthen the interaction [16,20]; or to enhance the expressiveness of touched objects [20,35]; or to offer accessible interaction design for people with impairment [13].…”
Section: Tactile Textures Perceptionmentioning
confidence: 99%
“…Previous research demonstrated the ability for users to accurately recognize textures even when using different finger speeds [30]; or when perceiving simultaneous but different textures [29]; or when the size of the tactile texture is small [15,32]. Researchers have also investigated the semantic of perceived textures [9] and proposed different applications to strengthen the interaction [16,20]; or to enhance the expressiveness of touched objects [20,35]; or to offer accessible interaction design for people with impairment [13].…”
Section: Introductionmentioning
confidence: 99%